Penerapan Teknologi Mesin Pengaduk Adonan Bakpao Berbasis Paddle Mixer Untuk Meningkatkan Efisiensi Produksi Umkm Di Bidang Kuliner - Saragih, Darwan Edyanto; Sitopu, Joni Wilson; Sinaga, Arisandi Satryawan; Trialdi, Rori (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service program aims to improve the efficiency and quality of production of dough-based food Micro, Small, and Medium Enterprises (MSMEs) through the implementation of a paddle-type bakpao dough mixer with a capacity of 10 kg/hour in Pematangsiantar City. The activity began with identifying the problems of partners who still rely on manual mixing processes, which results in long production times and inconsistent dough quality. The community service team designed a machine based on a 0.5 HP electric motor with a pulley-V belt transmission system and a horizontal mixer made of food-grade stainless steel. After undergoing training and mentoring, partners were able to operate the machine independently. Evaluation results showed that the use of the machine was able to reduce mixing time from ± 30 minutes to ± 12 minutes per batch and produce a more homogeneous dough. In addition to increasing time efficiency, there was an increase in production capacity and a potential increase in daily income by 30–50%. This activity not only presented applicable technical solutions but also strengthened partners' production capacity in a sustainable manner. This program proves that the integration of appropriate technology and a participatory approach can encourage MSME independence and expand the socio-economic impact based on local innovation.